Perancangan Sistem Keamanan Komunikasi Data pada Jaringan LoRA Menggunakan Algoritme PRESENT - Hikmaturokhman, Alfin; Ramadhani, Eka Hero; Wulandari, Asri (Yayasan Petra Harapan Bangsa, 2024)
LoRa is a low-power wireless communication technology capable of transmitting data over long distances. LoRa is widely used in embedded systems and the Internet of Things (IoT) in various sectors, such as agriculture, fisheries, industry, transportation, and smart cities. However, the data transmitted through LoRa is not encrypted, so the confidentiality of the data is not guaranteed because the data can be intercepted and read by hackers at the same frequency. Therefore, data encryption techniques are needed in the LoRa system to maintain data confidentiality when transmitted. In this research, a LoRa system is designed, and an analysis of the lightweight PRESENT block cipher algorithm is carried out to secure data communication on the LoRa system. This research uses a LoRa RFM95W module with a 915 MHz frequency and an ATmega328P microcontroller. This research method consists of the stages of literature study, design, implementation, testing, and analysis. After the design and implementation stages, the LoRa system was tested with data transmission test scenarios with test vectors and data communication interception tests. This research shows that the PRESENT algorithm was successfully implemented on the LoRa communication system, and hackers could not read the data sent from LoRa Tx and Rx. The test results also show that implementing the PRESENT algorithm on the LoRa system does not affect data communication performance based on RSSI values. The results of this research can be used in further research in various fields, such as IoT security in agriculture, fisheries, transportation, industry, and smart cities.